PENGARUH DAMPAK KELINGKUNGANAN DAN KEEFEKTIFAN KONSUMEN PERSEPSIAN PADA KESEDIAAN MEMBELI LEBIH MAHAL YANG DIMEDIASI OLEH NIAT MEMBELI PADA PEMBELIAN PRODUK HIJAU - Rika Resti Fausi; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the willingness to buy more expensive green products in the effect of the intention to buy green products. Data obtained through a questionnaire distributed to consumers of green products in Surakarta in a cluster. The sampling technique used was pur posive sampling of 200 respondents. Hypothesis testing uses Structural Equation Modeling (SEM) analysis and regression analysis with mediation. The results showed the intention to buy green products had a positive effect on the willingness to buy more expensive green products, the impact of the environment had a positive effect on the intention to buy green products, the effectiveness of perceived consumers had a positive effect on the intention to buy green products, the intention to buy green products strengthened the relationship between the impact of the environment and willingness to buy more expensive green products, and the intention to buy green products has a positive effect on the effectiveness of perceived consumers and willingness to buy more expensive green products.